Enhancing sustainable biogas production: bio-methanation of wastewater using ultrasonic-membrane anaerobic system (UMAS) - Suguna, Arumugam (2024)
This research investigates the use of an Ultrasonic Membrane Anaerobic System (UMAS) to enhance biogas production from palm oil mill effluent (POME). POME is a significant environmental pollutant generated during palm oil processing, characterized by high organic matter content. Conventional POME treatment methods often face limitations such as low efficiency and high operating costs. Anaerobic digestion is a promising approach for converting the organic matter in POME into biogas, primarily methane. However, membrane fouling remains a major challenge in conventional anaerobic membrane bioreactors (AnMBRs). This study aims to address these challenges by integrating ultrasonic technology with membrane bioreactors to improve the efficiency and sustainability of POME treatment. A 150L ultrasonic bioreactor system will be constructed and operated under controlled conditions to optimize biogas production and minimize membrane fouling. The performance of the UMAS will be evaluated by monitoring key parameters such as Chemical Oxygen Demand (COD), Biological Oxygen Demand (BOD), Total Suspended Solids (TSS), Volatile Suspended Solids (VSS), pH, and methane composition in the raw POME, reactor contents, and treated permeate. Fourier Transform Infrared Spectroscopy (FTIR) analysis will also be conducted to assess changes in the chemical composition of POME during the treatment process. The results demonstrate the effectiveness of the UMAS in reducing pollutant levels and enhancing biogas production, with the highest COD, BOD, TSS, and VSS removal efficiencies of 98.97%, 91.67%, 96.55%, and 93.86%, respectively, achieved on the 8th day of operation. Methane composition reached 93.33% on the same day, indicating efficient conversion of organic matter to biogas. This research highlights the potential of the UMAS to improve the efficiency and sustainability of POME treatment by enhancing biogas production and reducing environmental impact.